The implementation of 1 Student 1 Sport Policy among secondary school teachers in Kluang, Johor - Ahmad Mohamad Firdaus, Muhamad Tajul Arifin, Surat Shahlan, Hassim Jady Z., Lamat Siti Aida, (Universiti Pendidikan Sultan Idris, 2015)
The implementation of 1 Student 1 Sport Policy among secondary school teachers in Kluang, Johor by Ahmad Mohamad Firdaus, Muhamad Tajul Arifin, Surat Shahlan, Hassim Jady Z., Lamat Siti Aida,